2001
DOI: 10.1096/fj.01-0108com
|View full text |Cite
|
Sign up to set email alerts
|

Host nutritional selenium status as a driving force for influenza virus mutations

Abstract: Heterologous expression of the transient receptor potential-1 gene product (Trp1) encodes for a Ca2+ entry pathway, though it is unclear whether endogenous Trp1 contributes to a selective store-operated Ca2+ entry current. We examined the role of Trp1 in regulating both store-operated Ca2+ entry and a store-operated Ca2+ entry current, I(SOC), in A549 and endothelial cells. Twenty different 'chimeric' 2'-O-(2-methoxy)ethylphosphothioate antisense oligonucleotides were transfected separately using cationic lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
176
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(184 citation statements)
references
References 11 publications
6
176
1
1
Order By: Relevance
“…Further, they reported that Jasplakinolide, which induced cortical actin assembly and inhibited Ca ϩϩ entry, also disrupted the coupling of TRPC1 with the type II IP 3 R. 24 TRPC1 has been suggested to play a role in SOCE in a number of other cell types, including salivary gland cells, 45 A549 and pulmonary artery cells, 46 and vascular smooth muscle cells, 47 although the mechanism of gating in these cells has not been elucidated. Our studies present new evidence that supports an indirect role for TRPC1 in cation entry in platelets.…”
Section: Discussionmentioning
confidence: 99%
“…Further, they reported that Jasplakinolide, which induced cortical actin assembly and inhibited Ca ϩϩ entry, also disrupted the coupling of TRPC1 with the type II IP 3 R. 24 TRPC1 has been suggested to play a role in SOCE in a number of other cell types, including salivary gland cells, 45 A549 and pulmonary artery cells, 46 and vascular smooth muscle cells, 47 although the mechanism of gating in these cells has not been elucidated. Our studies present new evidence that supports an indirect role for TRPC1 in cation entry in platelets.…”
Section: Discussionmentioning
confidence: 99%
“…We used two different approaches to address this hypothesis: the lanthanide mineral Gd 3ϩ , used as a nonspecific cation channel blocker, and a low [Ca 2ϩ ] perfusate, used to directly test the requirement for Ca 2ϩ entry. Gd 3ϩ blocks store depletion-induced Ca 2ϩ entry via transient receptor potential channels, which have been characterized as putative store-operated channels (2,14,25). Gd 3ϩ is difficult to use in vivo since it binds avidly to albumin (3), which may limit its efficacy with respect to blockade of Ca 2ϩ channels.…”
Section: Discussionmentioning
confidence: 99%
“…According to this model, the extent of store depletion is conveyed to PM by protein 4.1N, which links the cytoskeletal protein, spectrin, to TRPC4 [260] . The latter, in turn, contributes pore-forming subunits to the store-dependent channel along with TRPC1 according to the following stoichiometry, 1 TRPC1 and 3 TRPC4 [203,217,260,261] . The association between the two subunits is favoured by Cav-1, which also recruits InsP3R1 into the membranal signalplex [262] .…”
Section: +(Rt-pcr)mentioning
confidence: 99%